THE EFFECT OF BENTONITE LEVELS ON TIME REQUIRED RH VALUE IN EQUALITY - Rizal, Muhammad; Arifin, Yulian Firmana (Universitas Lambung Mangkurat, 2023)
Negative pore water pressure is an indispensable indicator in unsaturated soil mechanics, so it has a very important function. Measurement suction becomes more important when dealing with bentonite which can be used in containment facilities and hazardous and radioactive waste remediation systems, or as an cover alternativemixing with respect to the time required to obtain equilibrium at the value of RH and temperature.There are 4 (four) combinations of material mixtures, namely the percentage of bentonite 5%, 10%, 15%, and 20% of the amount of claystone used. In mixing the samples, there were 2 mixing methods where the sample type A (claystone + water) + bentonite and simple type B (bentonite + water) + claystone with a dry density of 1.8 gr/cm3. The method used in this test is the capacitance relative humidity or the RH sensor.From the analysis, it is found that the value is influenced by factors ranging from water content where the time obtained is longer with increasing water content, the factor of bentonite where the less bentonite is given, the longer the time obtained. The measurement results are also used to predict the permeability of unsaturated soils. Keywords: Bentonite, Clay Stone, capacitance relative humidity, temperature